Service Quality Affecting Efficiency in Tax Collection of Kanchanaburi Area Excise Office - Thinsamran, Waranya (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The purposes of this research were to study service quality and efficiency in the tax efficiency of Kanchanaburi Area Excise Office in order to make a comparison of the service quality classified by personal factors and to study relations of the service quality The sample of this study were 400 clients at Kanchanaburi Area Excise Office by using quota random sampling. The instrument used in this study was a 5-level rating scale questionnaire with content validity between 0.64-1.00, reliability of the service quality of 0.93 and reliability of tax collection efficiency of 0.85. Statistics used in data analysis were percentage, mean, standard deviation, t-test, one-way ANOVA, and multiple regression with statistical significance at 0.05 The research results were as follows: 1. The clients’ opinions on the service quality of Kanchanaburi Area Excise Office was overall high. When considering in separate aspects, they all were found to be high. The clients placed an importance on trustworthiness the most. In addition, the efficiency in tax collection of Kanchanaburi Area Excise Office was overall high and when considering in separate aspects, they all were found to be high. The clients saw tax levied as aimed target as the most important. 2. The results of the comparison of efficiency in tax collection of Kanchanaburi Area Excise Office classified by personal factors showed that age, education levels, and average monthly incomes were statistically different. Meanwhile, it was found no difference when considered by gender and marital status. In Service the service quality affecting efficiency in tax collection of Kanchanaburi Area Excise Office, service quality, objectivity of services, trustworthiness and reliability, responses to clients, and recognition and understanding clients had an influence on efficiency in tax collection of Kanachanaburi Area Excise Office, whit statistical significance, multiple correlation coefficient (R2) equal to 0.71. It could be written as equations as follows: The efficiency in tax collection ŷ = 0.31 + 0.24X1 + 0.10X2 + 0.23X3 + 0.27X5 The predictive equation in form of standard scores is as follows: Zŷ = 0.24Zx1 + 0.10Zx2 + 0.23Zx3 + 0.27Zx5 Article history : Received 10 July 2019 Revised 23 November 2019 Accepted 28 November 2019 SIMILARITY INDEX = 7.41